2019
DOI: 10.1111/jac.12335
|View full text |Cite
|
Sign up to set email alerts
|

Growth and nutrition of cowpea (Vigna unguiculata) under water deficit as influenced by microbial inoculation via seed coating

Abstract: Drought can drastically reduce cowpea [Vigna unguiculata (L.) Walp.] biomass and grain yield. The application of plant growth‐promoting rhizobacteria and arbuscular mycorrhizal fungi can confer resistance to plants and reduce the effects of environmental stresses, including drought. Seed coating is a technique which allows the application of minor amounts of microbial inocula. Main effects of the factors inoculation and water regime showed that: severe or moderate water deficit had a general negative impact on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 64 publications
3
30
0
Order By: Relevance
“…Previous greenhouse studies reported benefits from AM fungi and PGPR, either inoculated by the conventional method (direct application in the soil) or through seed coating in cowpea performance. Nevertheless, there is still lack of information on the effect of AM fungi and PGPR, which can represent a significant barrier to up‐scale microbial applications .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous greenhouse studies reported benefits from AM fungi and PGPR, either inoculated by the conventional method (direct application in the soil) or through seed coating in cowpea performance. Nevertheless, there is still lack of information on the effect of AM fungi and PGPR, which can represent a significant barrier to up‐scale microbial applications .…”
Section: Discussionmentioning
confidence: 99%
“…Broadcasting of inocula of AM fungi and PGPR in open agricultural fields can be costly . Seed coating is considered a viable tool for precise and broad delivery of AM fungi and PGPR to different agricultural crops, and it has been explored in cowpeas under greenhouse conditions . This inoculation method allows the application of low amounts of inocula in combination with other exogenous ingredients onto the seed surface, resulting in close plant‐microbe contact at the early plant development stage.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the type of coating, specific equipment is considered [for some examples, see Pedrini et al (2017)]. The rotating pan is the most common device used for seed coating (e.g., pelleting, encrusting, dressing, and film coating) (Hartley et al, 2013; Oliveira et al, 2016a; Rouphael et al, 2017; Accinelli et al, 2018a; Rocha et al, 2019a; Rocha et al, 2019b). It usually consists of an inclined round pan rotating in slow motion, where materials are gradually added, followed by size sorting (sieving and screening) and then drying (Halmer, 2000; Pedrini et al, 2017).…”
Section: Seed Coating With Beneficial Microbesmentioning
confidence: 99%
“…Seed coating is a technique in which an active ingredient (e.g., microbial inoculant) is applied to the surface of the seed with the help of a binder and in some cases a filler that can act as a carrier. Seed coating has been proposed as a promising tool for inoculation of different crop seeds, since it is able to use minor amounts of inocula in a precise application (Jetiyanon et al, 2008; Oliveira et al, 2016a; Rouphael et al, 2017; Accinelli et al, 2018a; Accinelli et al, 2018b; Rocha et al, 2019a; Rocha et al, 2019b). The main types of seed coatings include seed dressing, film coating, and pelleting, which can be chosen differently, according to the purpose of application and the type of seed or selected microbes.…”
Section: Introductionmentioning
confidence: 99%
“…Seed coating is a process consisting on the application of exogenous materials (including inoculants) onto the seed surface and it has been considered a precise tool with the potential to deliver AM fungi to several agricultural crops, such as wheat, maize, artichoke and cowpea [23][24][25][26][27]. Seed coating ensures the contact of AM fungal propagules with emerging roots assuring colonization at the early plant development stage.…”
Section: Introductionmentioning
confidence: 99%